THE EFFECT OF ONLINE LEARNING MODEL ON COMMUNICATION ACTIVENESS IN CLASSROOM STUDENTS OF THE FACULTY OF EDUCATION AND TEACHER TRAINING UIN MAULANA MALIK IBRAHIM MALANG - Mukarromah, Siti Afifahtul (Proceeding of International Conference on Islamic Education (ICIED), 2021)
This research aims to determine the effect of online learning on the ability to communicate in class during learning. The study was designed by comparing communication activeness in online and offline learning. This research was conducted at UIN Maulana Malik Ibrahim Malang with population of all student faculty of education and teacher training UIN Maulana Malik Ibrahim Malang. The sample was probably 167 students. Data obtained by online questionnaire. Then the data were analyzed using the mann whitney u test. This research found that online learning influenced communication activeness in terms of asking questions. While the activeness of expressing opinions and arguing does not recognize the learning model.